The Role of Learning Loss Program in Improving Students' Learning in English Language in Public Schools in Ajloun Governorate from the Point of View of Principals - Al-Zghoul, Fatimah Hussien Mhmoud (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of Learning Loss Program in improving students' learning in English language in public schools in Ajloun Governorate from the point of view of principals. The researcher used the descriptive approaches. The sample of study consisted (90) female and male of school principals, chosen randomly. A questioner of (19) paragraphs is used in collecting the data divided into two sectors. The result of SPSS analysis has shown that the degree of the role of Learning Loss Program in improving students' learning in English language in public schools in Ajloun Governorate from the point of view of principals was moderated with average (3.60 out of 5) . The finding had shown that there were no statistically significant differences at (α≤0.05) refer to principal's sex (male and female). In addition, there were no statistically significant differences refer to principal's years of experience.
Keywords: Learning Loss Program; English Language; school Principals; Ajloun Governorate